Recent advances in twist drill design for composite machining: A critical review. (December 2017) - Ismail, Sikiru Oluwarotimi; Dhakal, Hom Nath; Dimla, Eric; Popov, Ivan
In the field of composite technology, inefficient and poor designs of twist drills contribute immensely to the challenges facing drilling of composite materials. An attempt to report some of the drill design methods and their inherent challenges confronting composite machining necessitates the writing of this article. A critical review has been conducted to offer a clear understanding of the current advances in the field of mechanical drilling of composite materials, focusing on geometry, material and parametric tool designs. The inter-dependable effects of thrust force, cutting speed, feed rate, cutting force and torque on drill design are similarly reviewed. This article also reveals other associated issues facing composite drilling including delamination, surface roughness, rapid tool wear and drill breakage. Well-designed drill geometry and good knowledge of drilling parameters afford the producers of polycrystalline diamond, carbide and high-speed steel tooling materials better opportunity of developing a drill that will minimise delamination of the reinforced composites and tool wear and produce a high-quality surface. Twist drill manufacturers and users will benefit from this article as they seek to have well-designed and improved drills.